Neck-to-height ratio is positively associated with diabetic kidney disease in Chinese patients with type 2 diabetes mellitus - He, Zhi-Ying; Gu, Xiao; Du, Lin-Jia; Hu, Xiang; Zhang, Xing-Xing; Yang, Li-Juan; Li, Ying-Qian; Li, Jing; Pan, Lin-Yu; Yang, Bo; Gu, Xue-Jiang; Lin, Xiu-Li (Frontiers in Endocrinology, 2023)
Introduction The aim of this study was to investigate the associations of neck circumference (NC) and neck-to-height (NHR) with diabetic kidney disease (DKD) in Chinese patients with type 2 diabetes mellitus (T2DM). Materials and methods A total of 2,615 patients with prevalent T2DM were enrolled. NHR was calculated through NC (cm) divided by height (cm), and prevalent DKD was defined as the urinary albumin-to-creatinine ratio (UACR) ≥ 30 mg/g or the estimated glomerular filtration rate (eGFR) < 60 ml/min per 1.73 m2 in the absence of other primary kidney diseases. Results The levels of NC and NHR were higher in DKD patients compared with non-DKD patients (38.22 vs. 37.71, P = 0.003; 0.232 vs. 0.227, P < 0.001, respectively). After full adjustments, individuals at the highest tertile of NHR had higher odds of DKD than those at the lowest tertile (multivariate-adjusted OR = 1.63, 95% CI: 1.22, 2.18), but this association was not pronounced with NC (multivariate-adjusted OR = 1.24, 95% CI: 0.87, 1.76). Individuals at the highest tertile of NHR had lower eGFR (β = -4.64, 95% CI: -6.55, -2.74) and higher UACR levels (β = 0.27, 95% CI: 0.10, 0.45) than those at the lowest tertile. The adverse association between NHR and prevalent DKD remained statistically significant among most of the subgroups analyzed and no interaction effects were observed. Conclusion The increase in NHR was adversely and independently associated with DKD in this Chinese T2DM population.